Cell-free circulating DNA integrity based on peripheral blood as a biomarker for diagnosis of cancer: a systematic review - Cheng, Jie; Tang, Qiuqiong; Cao, Xue; Burwinkel, Barbara (Cancer epidemiology, biomarkers & prevention, 2017)
Background: Cell-free DNA integrity (cfDI) has been identified as a potential diagnostic biomarker for different types of cancer, suggesting the importance of liquid biopsy. Methods: This systematic review aims to assess the diagnostic performance of cfDI in cancer. After an extensive search of literature published through February 28, 2017, 25 articles that included 40 studies were identified. The descriptions of all the studies were analyzed. The sensitivity, specificity, positive and negative likelihood ratios, diagnostic ORs, weighted symmetric summary receiver operating characteristic curve, and the area under the curve (AUC) of cfDI in these studies were calculated. Results: Aberrant results of cfDI were observed. Some studies observed an increased cfDI in cancer patients, while some studies confirmed a decreased cfDI compared with healthy or benign controls. Conclusions: This review suggests that cfDI is controversial as a blood-based biomarker of cancers, although the sensitivity and AUC were relatively high. Impact: cfDI shows heterogeneity between different studies; more perspective studies are needed to further assess its diagnostic performance, especially with other markers in combination. Cancer Epidemiol Biomarkers Prev; 26(11); 1595-602. ©2017 AACR.